Articular cartilage restoration using principles of tissue engineering - Abdul Rahman, Rozlin; A. Rahman, Nor Azlina; Sha'ban, Munirah (Open Access, 2013)
Articular cartilage has little capacity to repair itself. Any injury or degeneration of articular cartilage, be it a minor lesion may cause progressive damage and serious morbidity affecting people in every age group. In many cases, traditional surgical treatment has tasted its own success. However, tissue engineering has emerged as a potential treatment modality aiming to repair and regenerate the damaged articular cartilage. The aim of this review was to discuss the use of articular cartilage restoration using the principles of tissue engineering.